Case Report of snare-assisted coaxiality optimized technique during valve deployment in patient with pure aortic regurgitation - Yu, Jiwei; Du, Run; Ding, Fenghua; Zhang, Ruiyan; Zhu, Zhengbin (Frontiers in Cardiovascular Medicine, 2024)
In high-risk patients with pure native aortic regurgitation (PNAR), transcatheter aortic valve replacement (TAVR) remains an off-label intervention. Due to anatomical variations in the aortic root and technical challenges unique to PNAR, the transfemoral approach (TF-TAVR) requires continued accumulation of experience and technological refinement. In this context, we successfully and safely performed a snare-assisted TF-TAVR procedure for a patient with PNAR, characterized by significant aortic angulation. We introduced an innovative technique termed “snare-assisted coaxiality optimized technique” (SACOT) during valve deployment. SACOT played a crucial role in optimizing valve positioning, enhancing coaxiality, and achieving the ideal implantation depth for PNAR. Post-procedure assessments demonstrated stability and the absence of paravalvular regurgitation (PVR).